Labour market marginalisation in young refugees with and without common mental disorders. (30th September 2020) - De Montgomery, C; Norredam, M; Krasnik, A; Petersen, J H; Björkenstam, E; Berg, L; Hjern, A; Sijbrandij, M; Klimek, P; Mittendorfer-Rutz, E
Abstract: Background: This study explored how inequality in labour market marginalisation (LMM) between refugees and their peers developed during early adulthood in Denmark and Sweden (DK/SE), and the role of common mental disorders (CMD) in these trends. Methods: Using registry data, all refugees living in DK/SE in 2009-2012 who were born 1986-1993 and who immigrated as children (aged 0-17) were included (N = 13, 390/45, 687) and 1:5 matched on age, sex and municipality size to individuals born in DK/SE with at least one parent also born in DK/SE (N = 69, 650/227, 287). Information on psychiatric care (hospital and medicine) during 2009-2011 indicated CMD, while LMM was measured during 2012-2015 using income-based indicators. Probabilities of LMM were standardized by multiplying the estimated parameters of linear probability models in SE (adjusted for age, sex, municipality size, age of arrival, origin country, and accompanying family) onto the mean of the covariates in DK. Results: The risk of LMM was 2-2.5 times higher for refugees across ages 20-29 in DK/SE. The risk tended to decrease in SE but increased in DK for refugees. The increase was accentuated for youth with CMD. However, CMD did not explain the inequality between refugee and majority youth. The increase in DK was driven by birth-cohort differences, while the trend in SE was consistent across birth cohorts. Conclusions: CMD did not capture the vulnerability that sets refugees apart from their peers. While immigration and integration policy differences between DK and SE increased, the integration outcomes diminished, suggesting the importance of factors other than national level policies. Key messages: Young refugees in DK/SE were more at risk of labour market marginalization than their majority peers. Healthcare contact for common mental disorders raised levels, but did not reduce inequalities. Labour market marginalisation decreased with age in Sweden but increased for refugees in Denmark, driven by birth cohort difference.